2016
DOI: 10.3892/ol.2016.5369
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for EMT and MET in breast cancer: An update

Abstract: Abstract. Metastasis and recurrence are the leading cause of mortality due to breast cancer, but the underlying mechanisms are still poorly understood. Understanding the breast cancer metastasis mechanism is important for early diagnosis and treatment of breast cancer. The seeding and growth of breast cancer cells at sites distinct from the primary tumor is a complex and multistage process. Recently, it has been reported that the epithelial-mesenchymal transition (EMT) and the mesenchymal-epithelial transition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
79
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(82 citation statements)
references
References 97 publications
(99 reference statements)
3
79
0
Order By: Relevance
“…Furthermore, ten out of 11 pure spindle cases (WHO_5) assessed do not express E-cadherin, a finding consistent with the data of refs 30 and 31. The traditional, categorical dogma of an EMT, wherein vimentin switches on, while E-cadherin switches off [32], is not uniformly observed in these tumours, and indeed is likely to be different within the different morphological regions. It would be interesting to determine whether the transcriptional programme of EMT is also atypical in these tumours, as parallel studies of endometrial carcinosarcomas have identified differing miRNA programmes between the mesenchymal and epithelial components [33].…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, ten out of 11 pure spindle cases (WHO_5) assessed do not express E-cadherin, a finding consistent with the data of refs 30 and 31. The traditional, categorical dogma of an EMT, wherein vimentin switches on, while E-cadherin switches off [32], is not uniformly observed in these tumours, and indeed is likely to be different within the different morphological regions. It would be interesting to determine whether the transcriptional programme of EMT is also atypical in these tumours, as parallel studies of endometrial carcinosarcomas have identified differing miRNA programmes between the mesenchymal and epithelial components [33].…”
Section: Discussionmentioning
confidence: 91%
“…We demonstrated that nWdl could inhibit EMT by triggering molecular reprogramming in MDA-MB-231 cells, with enhanced efficiency compared with wedelolactone. In addition, nWdl modulated "cadherin switching," by increasing the expression of E-cadherin and reducing the expression of N-cadherin (42,43). Snail and Slug, which are known to regulate expression of E-cadherin in TNBC cells (44), were also regulated by nWdl.…”
Section: Discussionmentioning
confidence: 99%
“…Metastasis is the spread of tumor cells from their origin of formation. It is a multistep phenomenon that is initiated by EMT (Liu et al, ). EMT occurs when epithelial cells lose their connections with their environment and achieve a mesenchymal phenotype, assisting them to enter blood circulation and migrate to distant locations (Bill & Christofori, ; Felipe Lima, Nofech‐Mozes, Bayani, & Bartlett, ).…”
Section: Emt In Breast Cancermentioning
confidence: 99%
“…Both EMT and the CSCs of a BC are associated with changes in gene expression (Rich, 2016;Smith & Bhowmick, 2016). It has been recently demonstrated that epigenetic phenomena and non-coding RNAs are master gene regulators of EMT and CSCs that overlaps the invasiveness of cancer cells (Liu, Gu, Shan, Geng, & Sang, 2016;Zaravinos, 2015).…”
mentioning
confidence: 99%